Formulation of Appropriate Laws: A New Integrated Multidisciplinary Approach and an Application to Electronic Funds Transfer Regulation - White, Paul. author. aut Link
XXI, 178 p.
Keywords: Formulation of Appropriate Laws: A New Multidisciplinary Modelling Approach and an Application to Electronic Funds Transfer Regulation. Efficient laws have profound positive social, economic, political and welfare effects. As a consequence, the formulation of efficient laws is a central issue in the study, practice and implementation of laws. Fragmented approaches to the formulation of laws such as ‘comparative law analysis’ and ‘welfare economic analysis of laws’ exist in the current literature; they even occasionally rear their heads in the practice and implementation of laws. However, what these authors offer and what is needed, is an integrated approach to help formulate efficient and socially desirable laws – an approach that not only incorporates ‘comparative law analysis’ and ‘welfare economic analysis of laws,’ but also takes into consid- ation other various dimensions of human welfare that are affected by new laws and legal reform. This book presents such an approach using the Electronic Funds Transfer (EFT) regulation in Australia as its vehicle of analysis. The two-pronged approach offered in this book can be applied to formulate efficient laws that maximise the social welfare of the country, irrespective of social, political and economic organisations of the country under study. As such, this book makes several distinct contributions to the literature in law as it: 1. develops a new integrated multi-disciplinary approach using quantitative methods to formulate appropriate laws; 2. applies recent developments in welfare economics; 3.